Role of Rhamnolipid: A biosurfactant in methane gas hydrate formation kinetics - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Singh, Anil Kumar; Kumar, Pushpendra; Balomajumder, Chandrajit; Laik, Sukumar (Proceedings of The First International Conference on Recent Advances in Bioenergy Research, 2016)
Naturally occurring methane gas hydrate is a vast source of methane gas which is trapped in crystalline ice-like structure present in permafrost regions and under the sea in outer continental margins. It is purposed that total amount of carbon in the form of methane hydrates is almost twice the carbon content in all the fossil fuel reserves put together, and hence these are supposed to be the future potential energy resource. This paper investigates the laboratory investigations on effect of a biosurfactant rhamnolipid on methane hydrate formation kinetics. Rhamnolipid was produced by Pseudomonas aeruginosa strain A11. The presence of P. aeruginosa has been reported in Gulf of Mexico gas hydrate samples. Biosurfactant reduced the surface tension of water from 72 to 36 mN/m with CMC of 70 mg/L. The biosurfactant dose is studied at two different concentrations in the solution at 100 and 1000 ppm. Kinetic of hydrate formation and growth is compared at 0, 100, and 1000 ppm of rhamnolipid showing that rhamnolipid acts as a hydrate promoter at these concentrations. Thus, small dosages of rhamnolipids produced by P. aeruginosa strain A11 must clearly affect the gas hydrate formation kinetics in natural sites (as in Gulf of Mexico).
Keywords: Induction time; methane hydrate; Potential energy resource; Pseudomonas aeruginosa; Rhamnolipid